2014
DOI: 10.1371/journal.pone.0105017
|View full text |Cite
|
Sign up to set email alerts
|

The Immune System in Children with Malnutrition—A Systematic Review

Abstract: BackgroundMalnourished children have increased risk of dying, with most deaths caused by infectious diseases. One mechanism behind this may be impaired immune function. However, this immune deficiency of malnutrition has not previously been systematically reviewed.ObjectivesTo review the scientific literature about immune function in children with malnutrition.MethodsA systematic literature search was done in PubMed, and additional articles identified in reference lists and by correspondence with experts in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
489
5
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 503 publications
(532 citation statements)
references
References 219 publications
(407 reference statements)
26
489
5
12
Order By: Relevance
“…There is therefore an urgent need for further, larger studies of well-characterized cohorts of children with varying degrees of malnutrition, categorized according to current criteria, and followed longitudinally to probe immune function using modern laboratory techniques. Nevertheless, certain consistent findings from prior studies of immune function can be drawn from the literature, as comprehensively reviewed by Rytter et al [12]. The current paper will provide only a brief summary of these findings, before focusing on vaccination in the context of malnutrition.…”
Section: The Immunology Of Malnutritionsupporting
confidence: 60%
See 1 more Smart Citation
“…There is therefore an urgent need for further, larger studies of well-characterized cohorts of children with varying degrees of malnutrition, categorized according to current criteria, and followed longitudinally to probe immune function using modern laboratory techniques. Nevertheless, certain consistent findings from prior studies of immune function can be drawn from the literature, as comprehensively reviewed by Rytter et al [12]. The current paper will provide only a brief summary of these findings, before focusing on vaccination in the context of malnutrition.…”
Section: The Immunology Of Malnutritionsupporting
confidence: 60%
“…Scrimshaw et al [9] first described a vicious cycle of infection and undernutrition, whereby infections predispose to malnutrition, through reduced intake and absorption and diversion of nutrients away from growth, while malnutrition reduces immune function and increases the risk and/or severity of infections. Various iterations of this cycle have been proposed over the years, with more recent versions recognizing that subclinical infection, enteropathy, changes in the composition and function of the gut microbiota and systemic inflammation are likely to be important in the pathogenesis of malnutrition, in addition to overt infections [10][11][12]. Children hospitalized for severe acute malnutrition are extremely sick, with physiological dysfunction such as reduced respiratory muscle mass, impaired cardiac function and electrolyte disturbance, in addition to micronutrient deficiencies, inflammation, clinical infection and mucosal barrier breakdown.…”
Section: The Immunology Of Malnutritionmentioning
confidence: 99%
“…It appears in various forms, including impaired growth (e.g., stunting) and deficiencies in specific micronutrients (e.g., zinc, iron and vitamin A). Several abnormalities in immune function have been linked with malnutrition, including deficits in secretory IgA, complement production, gut barrier function and T-cell memory maintenance, among others [107]. In spite of these immunological deficits, a consistent link between malnutrition and oral vaccine performance has not been found [108,109].…”
Section: Malnutrition and Micronutrient Deficienciesmentioning
confidence: 99%
“…Malnutrition in some ways mimics intestinal failure and has been shown to account for severe infections (38). The various types of organ failure associated with malnutrition may contribute to immunodeficiency (39). It also has been suggested that specific vitamin deficiencies favor infectious diseases.…”
Section: Acquired Immunodeficiencymentioning
confidence: 99%